Protein corona-mediated transport of nanoplastics in seawater-saturated porous media. (1st September 2020) - Dong, Zhiqiang; Hou, Yuanzhang; Han, Wenhui; Liu, Mengping; Wang, Junliang; Qiu, Yuping
Abstract: The offshore aquaculture environment is a potential water area with high concentrations of tiny plastics and feeding proteins. In this study, the negatively charged bovine serum albumin (BSA) and the positively charged lysozyme (LSZ) were used to explore the effects of protein corona on the aggregation, transport, and retention of polystyrene nanoplastics (NPs; 200, 500, and 1000 nm) in sea sand saturated with seawater of 35 practical salinity units (PSU). The BSA corona, which was formed by the adsorption of BSA on the surface of NPs, drove the dispersion of NPs (200 and 500 nm) due dominantly to the induced colloidal steric hindrance. For example, the aggregate sizes of 500 nm NP decreased from 1740 ± 87 nm to 765 ± 8 nm at 40 min, which resulted in the enhanced transportation of NP. The calculated interaction energies indicated the BSA corona-induced high energy barriers (>10 4 KB T) between 1000 nm NPs and sand surface, demonstrating the BSA-enhanced transport of 1000 nm NPs. The mass percentage recovered from the effluent (Meff ) increased from 33.4% to 61.7%. Inversely, the LSZ corona triggered the aggregation of 200 nm NPs into the large aggregates via electrostatic adsorption and bridging effect, thereby inhibiting the transport of 200 nm NPs. Nevertheless, no LSZ corona was formed on the surface of 500 and 1000 nm NPs due to extremely low protein adsorption. Accordingly, LSZ cannot affect the stability and transport of these NPs. In the diluted seawater (3.5 PSU), the strong electrostatic attraction between positively charged LSZ and 500 nm NPs significantly increased and the LSZ corona formed, which induced the aggregation of 500 nm NPs. The Meff of NPs therefore decreased from 53.1% to 11.2%. Overall, the protein corona-mediated transport of NPs in seawater-saturated porous media depends on protein type, NP size, and seawater salinity. Graphical abstract: Image 1 Highlights: BSA and LSZ show different effects on the transport of nanoplastics (NPs). BSA–corona enhances NP transport (200-1000 nm) by steric repulsion. LSZ–corona induces 200 nm NP aggregation and inhibits its transportability. No change in NP transport (500 and 1000 nm) is due to lack of LSZ–corona.